Pre-post practice changes in countermovement vertical jump force-time metrics in professional male basketball players - Cabarkapa, D.; Cabarkapa, D. V.; Philipp, N. M.; Knezevic, O. M.; Mirkov, D. M.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2023)
Despite the countermovement vertical jump (CVJ) being one of the most popular noninvasive and time-efficient methods for monitoring neuromuscular status, there is a lack of scientific literature focused on examining fatigue-induced alterations in performance in elite athletes. Thus, the purpose of this study was to examine changes in force-time metrics pre-post practice in professional male basketball players. Seventeen athletes competing in first-tier and second-tier national basketball leagues in Europe participated in this study. While standing on a uniaxial force plate sampling at 1,000 Hz, each athlete completed 3 CVJs pre-practice and post-practice. The practice consisted of individual and team shooting drills, position-specific player development drills, 5-on-0 offensive actions, and 5-on-5 play, including full-court transition (~2 hours). The findings reveal that pre-post practice changes in force-time metrics seem to be phase specific. Despite a trivial increase in eccentric mean force (920.4 ± 100.2, 929.4 ± 100.0 N), most changes were observed within the concentric phase of the CVJ. The concentric phase duration increased pre-post practice (0.233 ± 0.027, 0.242 ± 0.033 seconds), whereas concentric impulse (262.9 ± 18.8, 258.6 ± 21.6 N·s), peak velocity (2.93 ± 0.22, 2.86 ± 0.22 m·s-1), mean force (2052.4 ± 179.2, 2002.7 ± 188.2 N), mean power (3,165.5 ± 269.5, 3,030.9 ± 326.8 W), and peak power (5,523.4 ± 607.3, 5,246.6 ± 663.7 W) experienced a significant decrease. Moreover, alongside longer contraction time (0.663 ± 0.065, 0.686 ± 0.074 seconds), lower vertical jump height (41.0 ± 6.8, 38.9 ± 6.6 cm) and reactive strength index-modified (0.634 ± 0.113, 0.579 ± 0.111 m·s-1) values were observed post-practice. Overall, these findings may allow practitioners to detect fatigue-induced changes in CVJ force-time metrics in professional male basketball players that can ultimately improve the acute and longitudinal training-adaptation monitoring process.